Meningkatkan Prestasi Belajar Matematika Materi Pengukuran Menggunakan Metode Problem Based Learning di MI Muhammadiyah Wonoanti I - Dinia Eka Nurlia; Eka Danik Prahastiwi (YASIN, 2025)
Mathematical ability is a crucial aspect of education as it contributes to developing students' logical, critical, and analytical thinking skills. However, mathematics learning is often perceived as difficult and monotonous by students, especially in measurement topics. This perception negatively impacts students' academic performance. This study aims to improve the mathematics achievement of fourth-grade students at MI Muhammadiyah Wonoanti 1 through the application of the Problem-Based Learning (PBL) method. PBL was chosen because it provides more contextual and challenging learning experiences, encouraging students to think independently in solving problems. This study employed a classroom action research (CAR) approach conducted in two cycles, including planning, implementation, observation, and reflection stages. The results indicate a significant improvement in students' academic performance, demonstrated by an increase in the class average score and active student participation during the learning process. Many changes and improvements were observed in the students. The students' average learning scores increased from 42.86% to 57.14% in the first cycle and rose further to 85.71% in the second cycle. Additionally, the learning environment became more interactive and enjoyable. Thus, the implementation of the Problem-Based Learning method proved effective in enhancing mathematics learning outcomes, particularly in measurement topics.